Calibrating Students’ Performance in Mathematics: A Rasch Model Analysis - Shamsuddin, Hasni; Abdul Razak, Nordin; Zamri Khairani, Ahmad (International Journal of Engineering and Technology, 2018)
Rasch model analysis is an important tools in analysing studentsâ€™ performance at item level. As such, the purpose of this study is to calibrate 14 years old studentsâ€™ performance in mathematics test based on the item difficulty parameter. 307 Form 2 students provide responses for this study. A 40-item multiple choice test was developed to gauge the responses. Results show that two of the items need to be dropped since they did not meet the Rasch modelâ€™s expectations. Analysis on the remaining items showed that the students were most competent in item related to Directed Numbers (mean = -1.445 logits), while they are least competent in the topic of Circle (mean = 1.065 logits). We also provide calibration of the performance at item level. In addition, we discuss how to the findings might be helpful for teachers in addressing studentsâ€™ difficulty in the topics.Â Â